ANALYSIS OF THE EFFECT OF SALES PROMOTION, CUSTOMER SATISFACTION AND PRODUCT INNOVATION ON CUSTOMER LOYALTY OF DIGITAL WALLET SERVICES - Muthi’atul Khasanah; M. Wahab Khasbulloh; Silvia Ekasari; Muammar Afif Al Qusaeri; Slamet Riyadi (Sean Institute, 2023)
In particular, factors including product innovation, sales promotion, and customer happiness that have an impact on customer loyalty are the focus of this study. Purposive sampling was used in this study's data collecting process. This survey had 129 respondents in total. A questionnaire that has previously undergone validity and reliability testing was used to obtain the data. Multiple linear regression analysis was used to analyse the survey findings. The Sequential Explanatory Combination Method is used in this kind of study. According to the analysis's findings, customer contentment, sales promotions, and product innovation all have an impact on a customer's loyalty. Customer happiness, product innovation, and marketing all have an impact on a customer's loyalty.